The Influence of Green Marketing, Brand Trust, and Perceived Quality on Consumers Purchase Intention: Evidence from The Body Shop in Samarinda, Indonesia - Rr. Puspita Aprillia Kartini; Sugeng Raharjo (FEB Universitas Mulawarman, 2025)
Researching purchase intentions in the context of environmentally friendly products is important because the effectiveness of green marketing and consumer trust levels determine the extent to which sustainability messages can influence purchasing decisions. This study examines the impact of green marketing, brand trust, and perceived quality on consumers' purchase intentions for The Body Shop products in Samarinda. The research is motivated by the growing shift toward sustainability-based marketing and the inconsistent empirical findings surrounding consumers' intentions to purchase environmentally friendly products. Using a quantitative approach, data were collected from 130 respondents who were familiar with or had purchased The Body Shop products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that green marketing has a positive and significant impact on purchase intention, while perceived quality also exhibits a significant positive influence. In contrast, brand trust exhibits a positive but non-significant effect, indicating that trust alone may not be sufficient to drive behavioral intention in this context. These findings contribute to the understanding of green consumer behavior in emerging markets and offer practical insights for firms seeking to strengthen sustainability-driven marketing strategies